A systems approach to developing a port community system for South Africa - Sphiwe Eugene Mthembu; Mihalis Georgiou Chasomeris (Journal of Shipping and Trade (JST), 2022)
Port community systems (PCS), as electronic platforms enabling the intelligent and secure exchange of information between public and private stakeholders in ports, are central to port supply chains. PCS drive productivity, efficiencies, and competitiveness whilst improving the port's attractiveness. They connect port users and supply chain participants and allow them to share information efficiently on a single platform by drawing data from different enterprise resource management systems. Port systems are complex networks of functions integrated to deliver cargo services to port users. Developing countries' ports have suffered adversely from their slow adoption of PCS; consequently, their performance improvements have stagnated over time. This article uses Soft Systems Methodology and applies it to the case of South Africa's ports that are particularly affected by the absence of PCS. The article also presents a framework for implementing PCS. Primary data was gathered through 24 interviews and two port stakeholder workshops. The findings show that port users are operating on fragmented and different platforms, lack integration and collaboration, and no single platform is used to share critical shipping information. Nevertheless, the interviewees all supported the creation of a PCS, and this article develops and recommends a framework for implementing a PCS in South Africa.
Keywords: 650; Port community systems; Soft systems methodology; Maritime; Ports; Information systems; Supply chain; Integration